2019
DOI: 10.3389/fmicb.2019.00685
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective Co-chaperone BcBAG1 Is a Component for Fungal Development, Virulence, and Unfolded Protein Response (UPR) of Botrytis cinerea

Abstract: The Bcl-2 associated athanogene (BAG) family is an evolutionarily conserved group of co-chaperones that confers stress protection against a variety of cellular insults extending from yeasts, plants to humans. Little is known, however, regarding the biological role of BAG proteins in phytopathogenic fungi. Here, we identified the unique BAG gene ( BcBAG1 ) from the necrotrophic fungal pathogen, Botrytis cinerea . BcBAG1 is the homolog of Arabidopsis thal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…Both proteins are related to UPR and apoptotic signaling. Bcire1 is known to be a core regulator of unfolded protein response (UPR) during ER stress in B. cinerea [ 37 ]. In yeast, it was previously reported that Ire1 is an activator of the UPR pathway that promotes the activation of the chaperone gene transcription, such as Lhs1, to relieve the ER stress, avoiding apoptosis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both proteins are related to UPR and apoptotic signaling. Bcire1 is known to be a core regulator of unfolded protein response (UPR) during ER stress in B. cinerea [ 37 ]. In yeast, it was previously reported that Ire1 is an activator of the UPR pathway that promotes the activation of the chaperone gene transcription, such as Lhs1, to relieve the ER stress, avoiding apoptosis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…lycopersici. Botrytis cinerea secretes an exopolysaccharide that can stimulate the SA signaling pathway of the host (Zhang et al, 2019;Tilocca et al, 2020). Due to the antagonistic relationship between SA and JA, the JA signaling pathway of the host is thus inhibited (Guzmán-Guzmán et al, 2017;Liu et al, 2019).…”
Section: Effector Proteinsmentioning
confidence: 99%
“…Most studies reported that BAGs regulate processes from pathogen attack to abiotic stress such as cold, drought, and salt and are involved in cellular responses based on the Ca 2+ /CaM signaling pathway [11]. However, less work has been conducted to demonstrate the influence of BAGs on plant growth and development [11,47].…”
Section: Discussionmentioning
confidence: 99%